Causes of sudden cardiac death in professional athletes - Kafara, Zuzanna; Jurczak, Dominika; Jonczyk, Agnieszka; Ambroży, Tadeusz; Muszkieta, Radosław; Makuch, Robert (Quality in Sport, 2025)
Introduction Extreme physical exertion, as experienced by professional athletes, tends to be a significant risk factor for adverse cardiovascular events, including sudden cardiac death (SCD). Despite advances in sports medicine, the precise impact of training intensity, duration, and functional adaptations on the development of cardiovascular disorders remains not sufficient. Moreover, individual predispositions play a crucial role in the manifestation of these conditions. Purpose This review aims to analyze the relationship between intense sports training and the risk of SCD with a focus on how different sports influence cardiac vulnerability. State of Knowledge To the most frequent causes of cardiac arrest in young athletes (≤ 34 years of age) belongs hypertrophic cardiomyopathy, and in the case of older sportsmen (> 35 years of age) it is ischemic heart disease. Pathological abnormalities of the cardiovascular system, inducing sudden cardiac death in professional competitors, are based on the mechanism of severe ventricular aberrations of cardiac rhythm, i.e. ventricular fibrillation and tachycardia. Conclusions Sudden cardiac death in athletes is a complex issue influenced by multiple factors, including genetic predisposition, training intensity, and the type of sport performed. A better understanding of the mechanisms leading to SCD are essential for developing effective preventive strategies.